Study the role of auxins and sytoknins on in vitro propagation of Spilanthes acmella (L.) Murr (Baghdad Science Journal, 2014)
The technique of plant tissue culture has been used to In vitro micropropagation of Spilanthes acmella (L.) Murr. It is an ornamental and medicinal plant not cultivated in Iraq. Seeds were sterilized and cultuared on full strength Murashige and Skoog medium(1962)(MS). Naphthalene acetic acid (NAA), 6- furfuryl aminopurine (Kin.) growth regulators were used at the Initiation stage.The combination between IAA and Kin. was used in multiplication stage. IAA was used for rooting the shoots. Results showed that 1.5% sodium hypochlorite for 15 min was very effective for disinfecting and survival. Nodes exhibited relatively highest response as compared with apical meristems and leaflets culture. Supplying the culture medium with 1 mg/L. Kin. was effective for lateral shoot induction. The mean number of shoots obtained from nodes were 4.12 with a mean length 2.70 cm. Adding Kin. at 0.5, 1.0 or 1.5 and IAA at 0.1 mg/L. to the growth medium was effective for multiplication. Mean number of the developed shoots were 13.60, 14.20, 12.00 respectively. The best result of rooting stage was achieved by half- strength MS medium without growth regulators which produced 27.50 roots/ plantlet with mean length 3.90 cm. Results of acclimatization stage showed that addition of 1:1 peat moss and loamy soil gave the highest rate of survival(100)% after 4 weeks of acclimatization. This study showed the ability of in vitro propagation of Spilanthes acmella (L.) Murr.